2003
DOI: 10.1001/archneur.60.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Increased Brain β-Amyloid Load, Phosphorylated Tau, and Risk of Alzheimer Disease Associated With an Intronic CYP46 Polymorphism

Abstract: CYP46 influences brain beta-amyloid load, cerebrospinal fluid levels of beta-amyloid peptides and phosphorylated tau, and the genetic risk of late-onset sporadic AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
116
6
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(133 citation statements)
references
References 30 publications
9
116
6
2
Order By: Relevance
“…However, these association studies have shown inconsistent results concerning variations in the CYP46A1 gene and the risk of AD (Desai et al, 2002;Helisalmi et al, 2006;Ingelsson et al, 2004;Papassotiropoulos et al, 2003). In addition a meta-analysis of the available data does not support a link between genetic variations in CYP46A1 and the risk of AD (Llorca et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these association studies have shown inconsistent results concerning variations in the CYP46A1 gene and the risk of AD (Desai et al, 2002;Helisalmi et al, 2006;Ingelsson et al, 2004;Papassotiropoulos et al, 2003). In addition a meta-analysis of the available data does not support a link between genetic variations in CYP46A1 and the risk of AD (Llorca et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Intronic polymorphisms in CYP46A1 have been suggested to affect the load of both β-amyloid and phosphorylated tau protein in the brains of AD patients (Johansson et al, 2004;Papassotiropoulos et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This "volume advantage" affords the individual greater physical resistance against neural degeneration. Thus, CYP46 T-alleles might mediate a risk for AD (Helisalmi et al, 2006;Papassotiropoulos et al, 2003). The suggestion of a protective role of the CYP46 Calleles (SNP rs754203) is supported by recent findings in a Chinese population.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, previous studies showed that brain β-amyloid load and cerebrospinal fluid levels of phosphorylated tau protein in AD patients with the CYP46A1 gene TThomozygotes genotype were significantly higher than in subjects without the TT-homozygotes genotype. Therefore, polymorphism of the CYP46A1 gene may be involved in the pathogenesis of AD by regulating β-amyloid generation indirectly (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, polymorphism (T/C, rs754203) in the CYP46A1 gene is associated with an increased risk for AD along with increased beta-amyloid load in brain tissues and with increased cerebrospinal fluid levels of beta-amyloid peptides and phosphorylated tau protein was reported (14). In studies of the relationship between CYP46A1 gene polymorphism and AD risk, a single nucleotide polymorphism (SNP) T/C in the region rs754203 of the CYP46A1 gene has been identified, and a significant correlation with an increased risk for AD has been revealed.…”
Section: Introductionmentioning
confidence: 99%